Adaptive Synchronization of Delayed Chen Chaotic System - Fan, Tao; Chen, Chang-Zhong; Ren, Xiao-Hong; He, Ping (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we focus on the adaptive synchronization of delayed Chen chaotic systems with unknown parameters. An adaptive synchronization controller and the adaptive updating law are designed. At last, the numerical simulation is shown to prove the effectiveness of the proposed synchronization controller schemes.